Expression patterns of CD44 and AREG under treatment with selective Tyrosine Kinase inhibitors in HPV+ and HPV− squamous cell carcinoma - Kansy, Benjamin Alexander; Aderhold, Marc Christoph; Huber, Lena; Ludwig, Sonja; Birk, Richard; Lammert, Anne; Lang, Stephan; Rotter, Nicole; Kramer, Benedikt (Cancer genomics & proteomics, 2020)
Background: We investigated the expression patterns of cluster of differentiation (CD) 44 and amphiregulin (AREG), two signaling molecules essential for cell proliferation and differentiation, under the influence of selective tyrosine kinase inhibitors (TKIs) in human papillomavirus (HPV)+ and HPV− squamous carcinoma cell lines. Materials and Methods: The protein expression of CD44 and AREG was determined by sandwich enzyme-linked immunosorbent assay in HPV− cell lines UMSCC-11A and UMSCC-14C, and HPV+ CERV-196 cells after TKI treatment. Results: The expression of AREG and CD44 was dependent on the cell line's HPV status. AREG expression increased after incubation with nilotinib in HPV+ tumor cells. The expression of CD44 was significantly influenced by all drugs; its expression under selective epidermal growth factor receptor inhibition was mostly reduced, whereas nilotinib led to an exceptional increase of CD44 expression. Conclusion: The selective drug treatment options significantly influenced the expression of CD44 and AREG in HPV− and HPV+ tumor cells, constituting the need for personalized treatment options.